Hidrólise enzimática dos polissacarídeos do café - Baraldi, Ilton José (2013)
Instant coffee is one of the main products generated by food industry worldwide, consisting of solubilized fraction from roasted and grounded coffee by heat treatment in two steps: thermal extraction at 125 0C, followed by thermal hydrolysis at 180 0C of not solubilized fraction in the previous step. With a high overall yield (~ 50%) due to high temperatures used in thermal hydrolysis step in order to solubilize carbohydrates present in the coffee, this step is characterized by high energy consumption and generation of unwished volatile compounds (acetaldehyde, furfural and 5 -hydroxy methyl furfural) from thermal degradation of coffee beans constituents. The goal of this study was to evaluate the feasibility of conducting hydrolysis and solubilization of polysaccharides remaining in coffee residue after thermal extraction step (low temperature) through enzymatic hydrolysis. This alternative was further compared to the industrial process conventionally employed. Enzymatic hydrolysis experiments were performed at 50 0C and pH 5.0, using roasted arabica coffee residue obtained after thermal extraction conducted at 125 0C (Steps I and II) or at 165 0C (Step III). Solubilized fraction by thermal extraction, thermal or enzymatic hydrolysis were characterized in terms of volatiles from thermal degradation (GC-MS), carbohydrate composition (HPAEC-PAD) and sensorial evaluation. In Step I of this study, 11 commercial enzyme preparations, presenting enzymatic activities of galactomannanases, cellulases, galactanases and β-glucanases, among others, able to act in coffee biopolymers (arabinogalactans - AGs, galactomannans - GMs and cellulose) were tested. Three enzyme preparations (Powercell, Galactomannanase-HBI and Ultraflo® XL) were selected due to their high activity in standard substrates (463 FPU / g, 18,554 IU / g and 1.028 IU / mL, respectively). In Step II, the influence of the concentration of enzymatic preparations Powercell, Galactomannanase-HBI and Ultraflo ® XL (independent variables) on the performance of the enzymatic process was investigated by running 11 experiments performed according to a full factorial design in two levels. Results showed that Ultraflo® XL preparation did not contribute for carbohydrates solubilization nor for yield increasing (p-value> 0.49), while enzymes present in the preparations Galactomannanase and Powercell influenced significantly the response variables favoring the release of glucose, arabinose, mannose and glactose as free and total sugars (p-value <0.1). The best results were achieved in the experimental condition conducted with 0.12% of Powercell, 0.10% of galactomannanase, and 0.12% of Ultraflo® XL, reaching up 22.3% of yield with reduced concentration of unwished volatiles. Products obtained by the three processes were also compared, resulting in similar yields for thermal extraction and enzymatic hydrolysis, whereas thermal hydrolysis yield was approximately 60% higher, due to a high solubilization of galactose. However, this product contained double concentrations of unwished volatiles compounds. In order to improve the yield of the alternative process (thermal extraction followed by enzymatic hydrolysis), in Step III the extraction temperature influence in a range of 125 to 175 0C was studied. Results showed that it is possible to increase thermal extraction temperature to 165 0C, without additional generation of unwished volatiles and with 80% increase of yield in this stage, when compared to the traditional process performed at 125 0C. Residue unsolubilized at 165 0C was then processed by thermal hydrolysis (180 0C) and enzymatic hydrolysis in 3 different experimental conditions of factorial design performed in Step II. Achieved yields were similar in thermal and enzymatic hydrolysis (~ 28%). It was also noticed that increase of thermal extraction temperature enhanced coffee biopolymers solubilization by the enzymes action, again with reduced formation of undesirable volatiles. Sensorial evaluation of soluble coffees obtained by the different process was conducted. Product generated at 125 and 165 0C showed characteristics similar to roasted and grinded coffee fresh brew. Yet, thermal hydrolyzed products in Stages II and III stood out by high acidity, while the enzymatic hydrolyzed product showed characteristic strongly bitter in Step II and neutral characteristic in Stage III, although enzymatic hydrolysis can be improved it can be used for instant coffee production.